THE EFFECT OF ROLE PLAY TECHNIQUE AND PERSONALITY TYPES ON THE SPEAKING COMPETENCY OF THE ELEVENTH GRADE STUDENTS OF S WIRA HARAPAN TEGALJAYA - Retny, A.; Jayaputra, I.N. A; Ratminingsih, N.M. (Universitas Pendidikan Ganesha, 2017)
This research aimed at investigating the effect of role play technique and personality types on the speaking competency. Particulary, this research aimed at investigating whether or not between students who are taught by using role play and those who are taught by conventional technique there is (a) a significant difference in speaking competency; (b) a significant difference of speaking competency between extrovert students and introvert students; (c) an interactional effect of the implementation of teaching techniques and students’ personality types in speaking competency ; (d) a significant difference in speaking competency between extrovert students and (e) a significant difference in speaking competency between introvert students. This study was conducted at the eleventh grade students of SMK Wira Harapan Tegaljaya. To answer the research problems, 2x2 factorial designs was implemented. The collected data were analyzed descriptively and inferentially by using IBM SPSS Statistics. From the result of the study, it can be concluded that: (1) There is a significant difference of speaking competency between students who are taught by using role play technique and who are taught by using conventional technique, (2) there is a significant difference of speaking competency between extrovert students and introvert students, (3) there is no interaction effect between students personality and role play technique on students speaking competency. (4) there is a significant difference of speaking competency between extrovert students who are taught by using role play technique and those who are taught by using conventional technique and (5) there is a significant difference in speaking competency between introvert students who are taught by using role play technique and those who are taught by using conventional technique. These findings are expected to have important contribution to EFL speaking classroom in Indonesia especially for eleventh grade students in SMK Wira Harapan Tegaljaya.